2019
DOI: 10.3847/1538-4357/ab0201
|View full text |Cite
|
Sign up to set email alerts
|

The SAMI Galaxy Survey: Quenching of Star Formation in Clusters I. Transition Galaxies

Abstract: We use integral field spectroscopy from the SAMI Galaxy Survey to identify galaxies that show evidence for recent quenching of star formation. The galaxies exhibit strong Balmer absorption in the absence of ongoing star formation in more than 10% of their spectra within the SAMI field of view. These Hδ-strong galaxies (HDSGs) are rare, making up only ∼ 2% (25/1220) of galaxies with stellar mass log(M * /M ⊙ )> 10. The HDSGs make up a significant fraction of non-passive cluster galaxies (15%; 17/115) and a smal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
84
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 96 publications
(91 citation statements)
references
References 191 publications
(301 reference statements)
6
84
1
Order By: Relevance
“…They show a range of kinematic properties: from dispersion-dominated kinematics reminiscent of quiescent galaxies (and consistent with the outcome of mergers; Hiner & Canalizo 2015) to rotation-supported systems (e.g. Norton et al 2001;Pracy et al 2013;Owers et al 2019). Chen et al (2019) find that stellar kinematics depend on the location of the PSB regions within the target galaxy.…”
mentioning
confidence: 69%
“…They show a range of kinematic properties: from dispersion-dominated kinematics reminiscent of quiescent galaxies (and consistent with the outcome of mergers; Hiner & Canalizo 2015) to rotation-supported systems (e.g. Norton et al 2001;Pracy et al 2013;Owers et al 2019). Chen et al (2019) find that stellar kinematics depend on the location of the PSB regions within the target galaxy.…”
mentioning
confidence: 69%
“…Rowlands et al (2018) have used data from MaNGA to derive Star Formation Histories (SFHs) of different galaxy subpopulations finding that PSB regions are more common outside of the galaxy center, are preferentially found in asymmetric galaxies, and have lower gas-phase metallicity than other regions, consistent with interactions triggering starbursts and driving low-metallicity gas into regions at <1.5 effective radii. Owers et al (2019) used the Sydney-AAO Multiobject Integral field spectrograph Galaxy Survey (SAMI, Bryant et al 2015) data to characterise the rare (∼2% of galaxies with log(M * /M ) > 10) population of galaxies showing PSB features in more than 10% of their spectra. These galaxies are more frequent in clusters than in the low-density environments, representing 15% and 2% of non-passive galaxies, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, in low density environments the PSB signal is spread across the galaxies. The Owers et al (2019) study is the only one explicitly focused on cluster galaxies. 1 Also based on the analysis of the location of these galaxies within their clusters, they concluded that the galaxies recently entered the clusters and are currently being quenched by ram pressure stripping.…”
Section: Introductionmentioning
confidence: 99%
“…From studies of galaxies that are actively being quenched (e.g. Koch et al 2012;Poggianti et al 2017;Jaffé et al 2018;Owers et al 2019;Zabel et al 2019) we can identify signatures of the different quenching mechanisms in terms of differing timescales and spatial distributions for the shut-down of star formation (e.g. Schaefer et al 2019).…”
mentioning
confidence: 99%